Search depth, knowledge characteristics, and innovation performance - Jianfeng Wu; Yonggui Wang; Sichao Li (Journal of Chinese Management, 2014)
This study takes a contingent perspective regarding the relationships among a firm's technological search depth, the characteristics of its knowledge, and its product innovation performance. While a firm's search patterns directly influence innovative output, their effectiveness is moderated by the internal context of knowledge: knowledge depth, knowledge scope, and related technological opportunities. Findings from the US electrical medical device industry (1990 to 2000) provide general support for these arguments.
Keywords: 650; Search depth; Knowledge stock; Product innovation